THE MAIN CHARACTER’S NEUROTIC NEEDS IN THE NOVEL THE INVISIBLE MAN BY H. G. WELLS - Tamrin, Andi Febriana; Adveni, Miselin; Basri, Basri (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This study analyses the types of neurotic needs experienced by Griffin through three kinds of neurotic conditions, which indicate that he has a neurotic disorder. This study uses psychoanalysis social by Karen Horney's theory about the types of neurotic needs, namely the neurotic need for power, the neurotic need to exploit others, the neurotic need for self-sufficiency, and independence. This study aimed to determine the types of neurotic conditions experienced by Griffin. This research method uses descriptive qualitative. The data Source of this research is the novel The Invisible Man by H.G. Wells, published in 1897 but using the 2016 version, which consists of 250 pages and 28 chapters. Meanwhile, the instrument in this study is note-taking. The data analysis technique of this research uses the theory of Miles and Huberman, namely, data reduction, data presentation, and drawing conclusions and verification. This study found that Griffin experienced three types of neurotic needs: the neurotic need for power, the neurotic need to exploit others, the neurotic need for self-sufficiency, and independence, which proves that he has a neurotic disorder or mental disorder. Social, cultural, and childhood life are the factors that influenced Griffin in a way to experience some types of neurotic needs.